2019
DOI: 10.31384/jisrmsse/2019.17.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Overconfidence on Investor’s Investment Decision: Moderating Role of Risk Perception and Religiosity-A Survey of Pakistan Stock Exchange

Abstract: The principal objective of the study is to find out the impact of overconfidence on investor’s investment decisions and to know whether risk perception and religiosity moderately affect the relationship between the overconfidence and investor’s investment decision. Data is collected through a well-structured questionnaire. Systematic sampling is used, and the sample size is 156. Statistical results indicate a significant impact of overconfidence on investor’s investment decisions. For the moderating part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…However, this hypothesis has been rejected as the study found that overconfidence has an insignificant positive effect on the investment decisions of Generation Z investors in Padang. Contrary to previous studies by Rehmat et al, (2023), Purwidianti et al, (2023), Hussain, Rasheed, et al, (2021), andFahim et al, (2019), which found that overconfidence has a significant positive impact on investment decisions, these results suggest otherwise.…”
Section: The Effect Of Overconfidence On Investment Decisionscontrasting
confidence: 99%
“…However, this hypothesis has been rejected as the study found that overconfidence has an insignificant positive effect on the investment decisions of Generation Z investors in Padang. Contrary to previous studies by Rehmat et al, (2023), Purwidianti et al, (2023), Hussain, Rasheed, et al, (2021), andFahim et al, (2019), which found that overconfidence has a significant positive impact on investment decisions, these results suggest otherwise.…”
Section: The Effect Of Overconfidence On Investment Decisionscontrasting
confidence: 99%
“…Risk perception influences decision-making, with behavioral predispositions potentially reducing an individual's perception of risk (Fahim et al, 2019). This perception shapes choices, revealing the link between social preferences and investor decisions .…”
Section: Risk Perception and Investment Decision Makingmentioning
confidence: 99%
“…However, it does not necessarily mean that overconfidence leads to wrong investment decisions. Instead, it is argued that it only slows down investors' learning, and a modest amount of overconfidence may even contribute to the emergence of new ideas (Bernardo and Welch, 2001; Zhang and Zheng, 2015; Fahim et al. , 2019; Vuković and Pivac, 2021).…”
Section: Behavioral Factors In Financial Marketsmentioning
confidence: 99%